"ENCLOSURES WITH INCLUSION" VIS-À-VIS "BOUNDARIES" IN ANCIENT MEXICO. Issue 1 (2023) - Megged, Amos
Abstract: Recent in-depth research on the Nahua Corpus Xolotl, as well as on a large variety of compatible sources, has led to new insights on what were "boundaries" in preconquest Nahua thought. The present article proposes that our modern Western concept of borders and political boundaries was foreign to ancient Mexican societies and to Aztec-era polities in general. Consequently, the article aims to add a novel angle to our understanding of the notions of space, territoriality, and limits in the indigenous worldview in central Mexico during preconquest times, and their repercussions for the internal social and political relations that evolved within the Nahua-Acolhua ethnic states ( altepetl ). Furthermore, taking its cue from the Corpus Xolotl, the article reconsiders the validity of ethnic entities and polities in ancient Mexico and claims that many of these polities were ethnic and territorial amalgams, in which components of ethnic outsiders formed internal enclaves and powerbases. I argue that in ancient Mexico one is able to observe yet another kind of conceptualization of borders/frontiers: "enclosures with inclusion, " which served as the indigenous concept of porous and inclusive boundaries, well up to the era of the formation of the so-called Triple Alliance, and beyond.